PEMBERIAN ASAP CAIR TKKS DAN TRICHOKOMPOS PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Endang Sulistyanti RS; Ardian ' '; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
ABSTRACT The purpose of this research is to find out the interaction of TKKS liquid smoke application and trichocompost as well as finding the best concentration and dozage of chose on the growth of oil palm seedling (Elaeis guineensis Jacq.) at the main nursery. This research was carried out at the Agriculturural Faculty University of Riau Bina Widya Campus KM 12,5 Simpang Baru Tampandistrick, Pekanbaru at the height of 10 m above sea level. The research was 4 months star in September 2015 through January 2016. The research utilize CRD (Completely Roudomized Design) which 2 factors. First factor is the concentration of liquid smoke wich 6 level. Second factors is trichocompost dozage wich 2 level. Both factor gave 12 treatment combination and wich 3 replication there are 36 experimental units. Each experimental units 2 seedling so that there were 72 seedling. Parameters observed were the increase of seedling height, the increase of leaf number, the increase of hump diameter, leaf area an soil analysis. Data were analyzed statistically with variance and continued with Duncan New Multiple Range Test (DNMRT) at 5% level. The result of the research showed chat interaction of liquid smoke and trickocompost gave nonsignificant effect to the parameter of seedling height increase, leaf number increase, hump diameter increase and leaf area of seedling. The combination of treatment liquid smoke with 20% concentration and trichocompost of 124.5 g/plant dosage trend to increase the seedling height, leaf number increase and leaf area of oilpalm seedling. The application of liquid smoke 20% gave good effect on the increase of seedling height and leaf number of seedling. The application of trichocompost 124.5 g/plant gave good effect on seedling height increase leaf number increase and hump diameter increase of oilpalm seedling. Keyword : Oilpalm, TKKS Liquid Smoke, Trichocompost.